Current background state of soils in the Tisza River Basin, Ukraine - Sukharev, Sergii; Mariychuk, Ruslan; Symkanych, Olesya; Babilia, Tetiana (Frontiers in Environmental Science, 2025)
The territory of the Tisza River Basin has a complex geological and tectonic structure, also pronounced landscape zoning with different types of soil. The assessment of the actual background state of soils was carried out within the national natural parks in 0–20, 20–50, and >50 cm soil profiles in terms of the content of heavy metals (HMs) and the radioactivity of gamma-active radionuclides (RNs). The studied national nature parks are located in different landscape areas (mountains, foothills, and lowlands) with different tectonics, geology, and soil types. Comparison of data on the content of HMs in soils shows that the total concentration of HMs is low (gross content for the 0–20 cm profiles: Zn - 19.8 ÷ 30.1; Cu - 9.6 ÷ 14.1, Pb - 9.4 ÷ 15.8, Cd - 1.10 ÷ 1.76 mg⋅kg−1 and content of acid-soluble forms: Zn – 8.7 ÷ 13.2; Cu – 0.67 ÷ 1.01, Pb – 7.6 ÷ 12.8, Cd – 0.36 ÷ 0.58 mg⋅kg−1) with a characteristic increase from mountainous to lowland landscapes. Based on a comparison of the content of HMs in soil profiles and the migration coefficient, it was established that lead (concentrated in the profile 0–20 cm; the migration coefficient is about 81% for lowland landscapes) is of anthropogenic origin, while other HMs are of natural origin. The results of radiological studies show that the radioactivity of technogenic 137Cs in soils is not high (13.5 ÷ 24.8 Bq⋅kg-1) with a characteristic increase from mountainous to lowland landscapes. The difference in the radioactivity of natural RNs (238U and 232Th series) for soils of different landscape zones is characteristic. For soils of mountainous landscapes, the total radioactivity of natural gamma-active RNs (excluding 40K) is significantly higher (254 ± 27 Bq⋅kg−1) than for foothill (239 ± 52 Bq⋅kg−1) and lowland (106 ± 38 Bq⋅kg−1) soils. This is obviously related to the tectonic activity of the young Carpathian Mountains. At the same time, the ratio of the sums of radioactivity of RNs of the 232Th and 238U series (Σ 232Th/Σ 238U) differs significantly for soils of different landscape zones. In the soils of mountain zones, natural RNs of the 238U series (Σ 232Th/Σ 238U = 0.87 ± 0.19) predominate, while in the foothills (Σ 232Th/Σ 238U = 2.26 ± 0.41) and lowlands (Σ 232Th/Σ 238U = 2.32 ± 1.47), RNs of the 232Th series predominate.